Digital Humanities and Portuguese Processing: a research pathway - Vieira, Renata (2022)
This paper reflects on the whole path of work in digital humanities, on the light of the projects related to text processing under development at CIDEHUS. These projects deal with a rich heritage related to the Portuguese culture, history and language. This paper reflects on the many challenges to be faced and how NLP techniques may broaden the capabilities of organising and sharing knowledge related to these resources.